La educación inclusiva: una vía para la integración (2012)
This article presents some theoretical guidelines, supported by best practices, which provide new insight into the design of educational policies that promote the construction of a new citizenship, at the same time this leads to social cohesion and integration of citizens. We started from a critical analysis of the compensatory measures in education that are carried out in Spain and we presented the inclusive education, highlighting the Learning Communities, as a model based on equal opportunities and results, which guarantees the access to education and its quality. We argue thereby an alternative way to manage diversity within the school, which basically focuses on equality, by ensuring that all students reach levels of excellence, and on integration, as key elements to make migratory movements promote human development.